Factors associated with motivation of employees toward training :a case study in Malaysia Airports sdn. bhd.,kuching international airport - Debra Leonie ak, Cosmas. (Universiti Malaysia Sarawak, UNIMAS, 2007)
The purpose of this study was to determine the motivation of employees toward training and factors influencing their motivation toward training. The dependent variable in this study was motivation of employees toward training while the independent variables were organizational commitment, perceived importance of training, supervisor support, and organizational culture. A survey methodology and an instrument of questionnaire in the form of Likert Scale type were used to obtain data from 55 respondents from a total population of 340 employees of Malaysia Airports Sdn. Bhd., Kuching International Airport. The characteristics of the respondents were described in terms of their age, gender, academic qualification, length of service, and unit of service. Pearson correlation test was used to determine the relationship between organizational commitment (r=0.438, p<0.01), perceived importance of training (r=0.581, p<0.00), supervisor support (r=0.576, p<0.00), organizational culture (r=0.475, p<0.00) and motivation of employees toward training. Findings of this study showed that there were significant relationships between all these factors with motivation of employees toward training. Stepwise multiple regression analysis was also used to determine the dominant factor influencing motivation of employees toward training. Findings showed that perceived importance of training as the dominant factor influencing motivation of employees toward training.Findings of this study can help the management of Malaysia Airports Sdn. Bhd., Kuching International Airportunderstand and predict the motivation level of the employees towards the organizations’ HRD activities.